The value of systematic follow-up imaging for assessing pseudoaneurysm formation after blunt and penetrating liver injury: A level 1 trauma centre experience. (April 2023) - Patel, Neeral R; Mehdi, Aia S; Sandhu, Amandeep; Mallon, Dermot; Dick, Elizabeth; Batrick, Nicola; Kashef, Elika
Introduction: Hepatic pseudoaneurysm (HPA) is a rare but potentially life-threatening sequelae of blunt or penetrating liver trauma. At our institution, an imaging protocol for liver injury patients has been developed, with repeat computed tomographic (CT) angiography of the liver 48–72 h post-admission to assess for HPA. The purpose of this study was to evaluate the utility of this imaging pathway in liver trauma for the detection of HPAs. Methods: A retrospective analysis was performed on patients who were admitted to our institution between January 2014 and January 2018, found to have either blunt or penetrating liver injury on initial CT imaging. Data collection included mechanism of injury, injury severity score (ISS), American Association for the Surgery of Trauma (AAST) liver injury score, initial and follow-up CT findings and secondary intervention. Results: During the study period, 149 major trauma patients were admitted with liver injuries (mean age 35.6 years; 72% male, 28% female). Seventy two percent of patients suffered blunt (median ISS = 29; median AAST = 2.89) and 28% patients suffered penetrating injuries (median ISS = 16; median AAST = 2.88). The mean time to follow-up CT was 46.1 h. Follow-up CT identified 8 (5.4%) HPAs. 5 (62.5%) of these patients were treated with embolization. ISS and AAST were not associated with pseudoaneurysm formation according to logistic regression analysis; however, ISS (OR 1.06 [1.02, 1.09; p < 0.05]) and AAST (OR 2.24, [1.31, 3.83; p < 0.05]) were associated with requirement for embolization. Conclusion: Our experience indicates a role for early detection of HPAs using a dedicated trauma imaging pathway.